Interpretations of Contemporary Society (Docentes 2.0 Journal, 2025)
Modernity is a historical period characterized by its emphasis on reason, science, progress, freedom, and human emancipation. The objective of this research was to analyze the main characteristics, problems, and challenges of modern and postmodern society, drawing on the perspectives of various authors who have reflected on its impact on social and educational life. The research was framed within the hermeneutic paradigm, employing an interpretive method, a qualitative approach, a critical narrative design based on documentary and bibliographic analysis, and a cross-sectional study design. The study sample consisted of seven academic and philosophical texts representative of modern and postmodern thought. Document analysis techniques and a categorization table were used to organize the information. The analysis enabled the identification of patterns, tensions, and connections between the examined ideas. The discussion section contrasted the benefits and limitations of both approaches. The conclusion reached was that it is urgent to rethink education to balance technical development with emotional and social development, thus fostering the holistic development of future citizens.
Keywords: Modernity; postmodernity; grand narratives; McDonaldization; society